Elucidating the biochemical basis of interaction between tea mosquito bug, helopeltis antonii signoret (hemiptera:miridae) and cashew (anacardium occidentale) - Nimisha, T (Department of Agricultural Entomology, College of Horticulture, 2018)
Cashew is one of the important foreign exchange earning crops of India with an export value of Rs. 5,077 crores during 2016-17.Cashew production is not in tune with increase in area under its cultivation. Low productivity in cashew is mainly due to the incidence of pests and diseases. Among the insect pests, tea mosquito bug (TMB), Helopeltis antonii Signoret (Hemiptera: Miridae) is the most important. It causes 30-50 per cent yield loss and during outbreak situations even up to 100 per cent loss has been reported. Cashew varieties exhibit wide variation in response to TMB infestation. Hardly any variety has ever been recorded as resistant to TMB till date. However, a few accessions are reported to be capable of withstanding TMB infestation and hence have been grouped as less susceptible category. Understanding the basis of interaction between the bug and the cashew is a prerequisite in developing varieties resistant to TMB. The present study entitled “Elucidating the biochemical basis of interaction between tea mosquito bug, Helopeltis antonii Signoret (Hemiptera: Miridae) and cashew (Anacardium occidentale)” was undertaken at the Department of Agricultural Entomology, College of Horticulture, Vellanikkara during September 2017 to July 2018. The objective of the study was to understand the variation in secondary metabolites and defense enzymes in selected cashew varieties induced by tea mosquito bug infestation and to elucidate the secondary metabolite detoxification mechanisms in the pest. Three months old grafts of four cashew varieties viz., two from the highly susceptible category (Anagha, Madakkathara-1) and two from less susceptible category (Damodar, Raghav) were used to conduct the experiment. Female adult bug (0-24 h old) was allowed to feed on each variety for different time intervals of 6, 24, 48 and 72 h. The biochemical parameters such as protein, phenol, tannin and defense enzymes viz., polyphenol oxidase (PPO) and phenyl alanine ammonia lyase (PAL) in leaves of TMB infested and non infested cashew grafts were analysed before release (0 h) as well as at different intervals of release. Biochemical analysis of the released TMB (crude homogenate of whole insect) viz., variation in total protein, SDS PAGE profiling of TMB crude protein, detoxifying enzymes viz., carboxyl esterase, cytochrome P450, and glutathione-s-transferases (GST) were carried out before releasing on the plant and at different intervals after release. The total leaf protein was found to be highest in the less susceptible variety Damodar (0.9925 mg g-1) and the lowest in the highly susceptible Madakkathara-1 (0.6729 mg g-1). Total phenol content was highest in the less susceptible Damodar (69.834 mg g-1) and Raghav (67.207 mg g-1) and the lowest was recorded in Anagha (29.625 mg g-1). Regardless of the varieties, highest phenol content was recorded in samples taken after 72 h of TMB infestation. Tannin content was also high in the less susceptible varieties Raghav (4.420 mg g-1) and Damodar (4.276 mg g-1) while highly susceptible varieties Anagha and Madakkathara-1 recorded lower values. Irrespective of the varieties, the highest tannin content was recorded in samples before the release of TMB (6.662 mg g-1). Results of the present study revealed that, detoxifying enzyme specific activity of PPO was highest in Damodar (0.003158 EU g-1min-1) and observed lowest value in Anagha (0.001406 EU g-1min-1). Irrespective of the varieties, enzyme activity reached highest at 48 h of release (0.00367 EU g1min-1). PAL specific activity was highest in Madakkathara-1 (0.575 μg g-1 min-1) and lowest in Anagha and was on par with Raghav and Damodar. In SDS PAGE, the whole body homogenate of adult female TMB revealed presence of bands in the range of ̴ 63 kDa and 35-48 kDa in the early stage of infestation. However, as the exposure time increased, protein bands ranging from 17-75 kDa appeared. Defensive enzymes viz., carboxyl esterase and GST expressed elevated activity in TMB that fed on less susceptible Raghav (258.117 μmol min-1mg-1 protein, and 365.262 μmol min-1mg-1 protein respectively) and Damodar (208.916 μmol min-1mg-1protein, and 501.879 μmol min-1mg-1protein respectively) when compared to the highly susceptible varieties. Cytochrome P450 showed highest activity in TMB fed on Damodar (0.372 nmol min-1mg-1 protein) and it was having lowest activity in insect fed on other three varieties. The study revealed that, the secondary metabolites viz., phenol, tannin and PPO have a definite role in imparting resistance in cashew to TMB attack. These metabolites have potential use in early detection of resistance in cashew against TMB. The enhanced levels of detoxification enzymes in TMB indicate plasticity of the pest against host plant defense and chance of resistance development against synthetic insecticides.